PENGARUH CORPORATE SOCIAL RESPONSIBILITY PT WANA PERINTIS TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA BARU KECAMATAN AIR HITAM (STUDI KASUS PT WANA PERINTIS) - Nurjannah Nurjannah; Maulana Yusuf; Muhammad Ismail (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The influence of PT Wana Perintis' CSR to improve community welfare. To achieve this goal, PT Raja Marga must optimize CSR distribution to the community so that CSR runs smoothly. This research aims to determine the impact of the Implementation of Social Responsibility (CSR) on Community Welfare in Baru Village, Air Hita District. This research uses quantitative methods, with a sample of 93 respondents who are residents of Baru Village. The sample determination method uses the Purposive Sampling method. The data in the research were collected through questionnaires which were processed and analyzed using simple linear regression analysis using the SPSS program. The results in this study show a sig value. of the CSR (X) variable of 0.000 is smaller (<) 0.05 and the result of the T-calculated value of the CSR (X) variable is 5.102 greater (>) than the T-table value of 1.986 which states that the influence of PT's CSR. Wana Perintis has a significant impact on community welfare. From the CSR program it can be concluded that the third CSR fund of PT. Wana Perintis can have a positive impact on improving welfare for the people of Baru Village.